Perceived knowledge and awareness of periodontal health amongst ante-natal mothers - Nurul Asyikin Y; Nor Shaida A; Nur Amirah Z (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
Physiological changes in the oral cavity and dental-related complications may occur during pregnancy. These intraoral changes that occur during pregnancy combined with lack of routine dental check-ups and delays in treatment for oral disease, place pregnant women at higher risk for dental infections. The objectives of this study was to assess the knowledge and awareness of pregnant women on periodontal disease and its effect on pregnancy, to investigate the relationship of their knowledge and awareness with level of education and the barriers of oral healthcare utilization among pregnant women. Methodology : A self-administered questionnaire with an introductory letter and consent form were given to pregnant women who came for their routine maternity check-up at the Obstetrics and Gynecology Clinic, Kuala Lumpur Hospital. Data entry and analysis was done using Statistical package for Social Sciences (SPSS) version 12. Result : Ninety-two pregnant women responded to the questionnaire. Only 23.9% answered correctly to the question on what is plaque. However, 45.7% knew that plaque can cause gum disease and a majority of the respondents 72.8% also knew that bleeding gum is an indication to inflamed gums. The result shows that, although 59.8% of the respondents were aware that it is necessary to brush their teeth frequently during pregnancy, only less than half of the respondents (44.6%) were aware that dental plaque and poor plaque control may cause periodontal disease among pregnant women. The majority (33.7%) feels that the long waiting time in the clinic would be their main barrier in seeking dental treatment. Conclusion : A majority of pregnant women have limited knowledge and poor awareness on periodontal disease and its effect on pregnancy.